Cytotoxicity assay-guided fractionation of Jatropha curcas L., (Fam. Euphorbiaceae) - Sijas, Jomhel P.; Taguibao, Jerson Jerick N.; Tan, Kate Angeline D.
Jatropha curcas L., or tubang bakod is a multipurpose shrub of the family Euphorbiaceae with a variety of agricultural, industrial and therapeutic utilities, while reports of acute toxicity have also been documented. The current study illustrates its promise as a source of cytotoxic drug with the three assays performed in conjunction with modified Kupchan fractionation. Initial in vitro cell susceptibility test confirmed the activity of extracts and fractions of leaves, stem bark, and roots. The brine shrimp (Artemia saliva) lethality assay identified the following fractions with appreciable activity: water fraction of leaf extracts (LW), dichloromethane and hexane fractions and crude extracts of stem bark (SD, SH and SC), and all five fractions and crude extract of roots (RW, RM, RB, RD, RH and RC). Among these, the dichloromethane and hexane fractions of stem bark extracts (SD and SH) possess the highest activity with mean IC of 0.0753 ug/ml and 1.4272 ug/mL determined by in vitro 96-well MTT assay of Saccharomyces cerevisiae (n=595 nm). Partial characterization by pytochemical screening strongly indicates that J. curcas glycosides, alkaloids, polyphenols and saponins are responsible for the cytotoxic activity. Further investigation to isolate the compounds responsible, to determine their mechanism, and to delineate between the safety and toxicity of J. curcas are recommended in order to evaluate its possibility for human use.
Keywords: Jatropha